(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the rate of surgical wound infection and analyze associated factors at Can Tho Orthopedic and Rehabilitation Hospital during the 2024–2025 period. Subjects and Methods: A cross-sectional descriptive study was conducted on 126 surgical patients at Can Tho Orthopedic and Rehabilitation Hospital from January 2024 to November 2025. Data were collected according to the infection control guidelines of the Ministry of Health and analyzed for the relationship between risk factors and surgical site infections. Results: The rate of surgical wound infection was 9.5%, with superficial infections accounting for 54.5% and deep infections for 45.5%; no infections in the cavity were recorded. Statistically significant associated factors with surgical site infections included: classification of the wound as infected/contaminated (p < 0.001), prolonged surgery duration (p = 0.026), diabetes (p < 0.001), preoperative hyperglycemia, increased white blood cell count, and high–very high NNIS score (p < 0.01), and the number of antibiotic groups used (p < 0.001). The group with a high–very high NNIS score had a surgical site infection rate of 66.7%. Conclusion: The rate of surgical wound infection in orthopedic surgery at the hospital is still relatively high. It is necessary to enhance preoperative risk assessment and strictly adhere to infection control measures.